A Minimally Invasive Approach to Left Ventricular Assist Device Insertion Facilitates Subsequent Explant. Issue 1 (January 2021) - Ziegler, Luke A.; Bittle, Gregory J.; Klass, Wyatt J.; Sorensen, Erik N.; Madathil, Ronson J.; Feller, Erika D.; Griffith, Bartley P.; Kaczorowski, David J.
A minimally invasive approach to left ventricular assist device (LVAD) insertion may benefit patients at the time of implant, but whether the approach to LVAD insertion influences the outcome of subsequent cardiovascular reoperations is unknown. Here we present the case of a 50-year-old male who underwent LVAD insertion through a minimally invasive approach and subsequently had left ventricular recovery. LVAD explant was performed without the use of any blood products or inotropic support. This case demonstrates that a minimally invasive approach to LVAD insertion may also facilitate subsequent device explant.